USO DE BUILDING INFORMATION MODELING PARA O APRIMORAMENTO E AUTOMATIZAÇÃO DO PLANEJAMENTO DE OBRAS: REVISÃO SISTEMÁTICA DA LITERATURA - Bezerra, Pedro; Scheer, Sergio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Planning is a process that allows the management of time, costs and resources required to carry out a project. The use of Building Information Modeling offers an alternative for the improvement of the planning process, due to the information provided by the models. Thus, the present article conducts a Systematic Review of the Literature to investigate how BIM technology can be used to improve construction planning automation. It was possible to analyze 20 recent publications dealing with the integration of information extracted from BIM models with various technological resources, helping in the process of decision making and organization of activities. The technological resources used were analyzed in four groups: metaheuristic algorithms, simulation software, programming languages and other less specific tools. Thus, it was possible to observe that the integration of these resources with the BIM-based data is able to automate several aspects of the planning process, such as organization of activities, site layout, scaffolding and even reuse of forms, optimizing both the time spent planning and the use of temporary resources.